A Low Profile Switchable Pattern Directivity Antenna using Circular Sectorized EBG - Mohamad Isa, Mohd Sa'ari; Awang Md Isa , Azmi; Mohd Zin, Mohd Shahril Izuan; Zakaria, Zahriladha; Nor Zaidi , Haron; Asmala, A. (Penerbit Universiti, UTeM, 2013)
In this paper, a low profile patch antenna switchable radiation pattern diversity with total thickness of